2012
DOI: 10.1371/journal.pone.0037483
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Systemic Inflammation is Associated with Poor Clinical Outcomes in COPD: A Novel Phenotype

Abstract: BackgroundBecause chronic obstructive pulmonary disease (COPD) is a heterogeneous condition, the identification of specific clinical phenotypes is key to developing more effective therapies. To explore if the persistence of systemic inflammation is associated with poor clinical outcomes in COPD we assessed patients recruited to the well-characterized ECLIPSE cohort (NCT00292552).Methods and FindingsSix inflammatory biomarkers in peripheral blood (white blood cells (WBC) count and CRP, IL-6, IL-8, fibrinogen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
544
1
24

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 688 publications
(596 citation statements)
references
References 43 publications
27
544
1
24
Order By: Relevance
“…First, the baseline inflammation levels and the dosage and time period of inhaled corticosteroid use were not recorded by us; for this reason, we can rule out a possible inflammatory pattern of response related to these factors. 33 Second, in white blood cell counts, data on the number of eosinophils were not collected; new research has found that these blood cells define a specific biologic cluster of patients with COPD exacerbation 34 and directly link corticosteroid treatment to exacerbation. 35 In conclusion, our study suggests that, in COPD patients, chronic use of inhaled corticosteroids does not influence per se the early inflammatory response to COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the baseline inflammation levels and the dosage and time period of inhaled corticosteroid use were not recorded by us; for this reason, we can rule out a possible inflammatory pattern of response related to these factors. 33 Second, in white blood cell counts, data on the number of eosinophils were not collected; new research has found that these blood cells define a specific biologic cluster of patients with COPD exacerbation 34 and directly link corticosteroid treatment to exacerbation. 35 In conclusion, our study suggests that, in COPD patients, chronic use of inhaled corticosteroids does not influence per se the early inflammatory response to COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Данные фенотипы характери-зуют различия между пациентами, страдающими ХОБЛ, связанные с клинически значимыми прояв-лениями и важными исходами заболевания. При этом различия в выраженности прогрессирования заболевания у пациентов с этими фенотипами вы-явлены не были [3,32,44]. В 2012 году испанское общество пульмонологов и торакальных хирургов усовершенствовало классификацию с использова-нием фенотипов, добавив рекомендации по уче-ту частоты обострений.…”
Section: клинико-анамнестические критерии прогрессирующего течения хоблunclassified
“…В развитии ХОБЛ большое значение имеют нару-шения защитной системы легких, включающей: клеточные механизмы (инфильтрация провоспа-лительными и эффекторными клетками тканей ре-спираторного тракта); гуморальные механизмы -(цитокиновая дисрегуляция и повышение продук-ции маркеров системного воспаления) и систему свободнорадикальных механизмов (оксидативный и нитрозивный стрессы) [3,13,14,35].…”
Section: персистирующее воспаление как основа прогрессирования хоблunclassified
See 1 more Smart Citation
“…COPD is a complex, multicomponent disease in which heterogeneity exists in a range of factors, including lung function decline, exacerbation frequency and the contribution of emphysema and small airways disease to airflow limitation [1,[8][9][10]98]. Addressing this heterogeneity is an unmet need in COPD management.…”
Section: The Future Of Copd Treatmentmentioning
confidence: 99%